Routine: digital finance application - Teo, Bobby (Nanyang Technological University, 2023)
This final year project proposes the development of an integrated finance management app that simplifies personal finance and investment tracking for users, making it an invaluable tool for individuals, families, and small startups. By addressing common barriers to expense tracking through intuitive features like categorised expense tracking, bill payment reminders, savings goal setting, and insightful spending habit reports, this app empowers users to regain control over their financial lives. Research suggests that diligent expense tracking leads to better budget adherence, increased savings, and reduced debt. In addition to personal finance management, the app offers a stock tracking function, enabling users to monitor stock prices and trends, helping them make informed investment decisions. Research has shown that users who utilise digital wealth management tools, including stock tracking apps, achieve higher average annual returns. The app is designed with a user-centric approach, ensuring it adds value by helping users achieve their financial goals and prioritising data security to protect users' financial information. In summary, this project seeks to create a comprehensive finance app that addresses financial challenges, enhances personal and investment success, and contributes to improved financial stability and wealth accumulation.